The Role of Islamic Microfinance in Reducing Poverty and Improving Community Welfare in Indonesia - Loso Judijanto; Dila Padila Nurhasanah; Salwa Aulia Novitasari (Westscience Press, 2025)
This study investigates the role of Sharia microfinance in reducing poverty and improving community welfare in Indonesia, using a quantitative approach. A total of 70 respondents, primarily micro-entrepreneurs and low-income individuals, were surveyed using a 1-5 Likert scale questionnaire. Data analysis was conducted using SPSS version 25. The results indicate that access to Sharia microfinance services significantly contributes to financial stability, vincome generation, and overall community welfare. Specifically, Sharia microfinance was found to improve financial security, enhance income opportunities, and promote social empowerment. These findings highlight the potential of Sharia microfinance as a tool for poverty alleviation and sustainable development. This research provides important insights for policymakers and microfinance institutions to enhance the effectiveness of Sharia-based financial services in promoting economic and social well-being.